Rotational Effects of Nanoparticles for Cooling down Ultracold Neutrons - Tu, Xiaoqing (Sci Rep, 2017)
Due to quantum coherence, nanoparticles have very large cross sections when scattering with very cold or Ultracold Neutrons (UCN). By calculating the scattering cross section quantum mechanically at first, then treating the nanoparticles as classical objects when including the rotational effects, we can derive the associated energy transfer. We find that rotational effects could play an important role in slowing down UCN. In consequence, the slowing down efficiency can be improved by as much as ~40%. Since thermalization of neutrons with the moderator requires typically hundreds of collisions between them, a ~40% increase of the efficiency per collision could have a significant effect. Other possible applications, such as neutrons scattering with nano shells and magnetic particles,and reducing the systematics induced by the geometric phase effect using nanoparticles in the neutron Electric Dipole Moment (nEDM), are also discussed in this paper.